Healthy Movement: Basic Health Check-ups and Mass Exercise at Bethesda Clinic Saribudolok (JURNAL PENGMAS KESTRA (JPK), 2025)
The elderly are a vulnerable group to non-communicable diseases (NCDs) due to decreased physiological function, limited physical activity, and low routine health check-up habits. This community service activity aims to improve early detection of health conditions, participation in physical activity, and health awareness for the elderly through the Healthy Movement program: Basic Health Check-up and Mass Exercise at the Bethesda Saribudolok Clinic. The method used is Participatory Learning and Action (PLA), which emphasizes the active involvement of participants through the stages of identifying health needs, basic health check-ups, elderly exercise, interactive education, and participatory reflection and evaluation. The activity targeted 23 elderly who participated in the entire series of activities. The results showed that 69.6% of the elderly were not accustomed to routine health check-ups. Blood pressure checks revealed that 52.2% of the elderly were in the pre-hypertension and hypertension categories, while body mass index measurements showed that 56.5% of the elderly were overweight and mildly obese. All participants (100%) completed the elderly exercise program, with 82.6% able to follow most of the movements. Health education increased understanding of the importance of regular checkups from 39.1% to 87.0%, and encouraged 78.3% of seniors to engage in regular physical activity. Participant satisfaction reached 91.3%, indicating excellent acceptance of the program. This program has proven effective in increasing awareness, participation, and understanding of senior health, and has the potential to become a sustainable, participatory, promotive-preventive community service model.